Programming actors with Akka : an introduction to actor systems, testing, failures, and integration patterns (O'Reilly, 2017)
"Reactive and asynchronous applications are growing in popularity, but what is the best way to build them? This course teaches you how to apply the latest concurrency techniques to develop state of the art Java applications. With the rise of microservices and service oriented architectures (SOAs), asynchronous concurrency is now critical to day-to-day Java development. This video builds on the theory offered in the associated 'Asynchronous Programming in Java' course by refactoring several Java projects using Actors in Akka. From there, it explains the concepts behind the actor model, how the Akka toolkit compares with other concurrency concepts, and how to use the Akka API."--Resource description page